Tinjauan Momen Lentur Pelat Dua Arah dengan Metode Perencanaan Langsung dan Metode Elemen Hingga - Fahri, Muhammad; Suyadi, Suyadi; Purwanto, Eddy (Jurnal Rekayasa Sipil dan Desain (JRSDD), 2016)
This research conducted to study and determine the bending moment plate by using the DirectDesign Method and Finite Element Method. In the procedure of calculation of concrete structuresfor buildings, namely SNI 2847 2013 has been set up several plates planning methods one ofwhich is a method of using the Direct Design Method analysis. Finite element method (FEM) isdividing a complex problem into small elements where a simpler solution can be easily obtained.The theory used in plate analysis with the FEM is Kirchhoff-Love theory in which the limits areused specifically for the analysis of thin plates with small deflections by ignoring the transverseshear forces. The program is used by applying the Finite Element Method in this study is aMicrosoft Excel as a tool for calculations and modeling program SAP 2000 as a plate structure.From the calculations that the value of deflection and the bending moment on the plate twodirections with varying results.From the results obtained show that the static moments of totalfactored Direct Planning Method and the Finite Element Method showed results equal to eachother . Distribution moments on the foundation and interior plate field differently due to directPlanning Method using a great moment coefficients in pedestal while the Finite Element Methodusing transition stiffness matrixKeywords:Direct Design Method, Finite Element Method, Two way slab, SAP 2000